Retrospective evaluation of left ventricular eccentricity index in the assessment of precapillary pulmonary hypertension in dogs (2017–2021): 145 cases - Graziano, Nicolas; Gommeren, Kris; Valcke, Annelies; Burnotte, Priscilla; Beeston, Dave; Walker, Tom; Gele, Rebecca; Lekane, Marine; Merveille, Anne Christine (Frontiers in Veterinary Science, 2025)
ObjectiveTo determine interobserver variability of left ventricular eccentricity indices measurements in systole (EIs), diastole (EId) and at maximum flattening (EIm) by emergency and critical care residents on prerecorded cineloops in dogs with or without pulmonary hypertension. To assess whether these EI measurements allow to identify dogs with right heart changes compatible with moderate to severe pulmonary hypertension (PAH).MethodsMulticenter, retrospective, case–control study from 2017 to 2021. Medical records of dogs with stage B1 myxomatous mitral valve disease (MMVD) and dogs diagnosed with precapillary pulmonary hypertension (PCPH) via echocardiograms were reviewed. Dogs were categorized by a cardiologist into five groups (normal, B1 MMVD, mild, moderate, and severe PCPH) based on Doppler pulmonary pressure gradients and right heart morphology. Four blinded emergency and critical care residents measured EIs, EId and EIm.ResultsOne hundred and forty-five client-owned dogs were included. Interobserver agreement was strong, with an intraclass correlation coefficient (ICC) of 0.737 (95% CI: 0.621–0.852) across all eccentricity indices for the full study population and 0.768 (0.642–0.856) for the PAH group specifically. EIs, EId, and EIm were significantly higher in the PAH group compared to control and MMVD groups (p < 0.0001). The differentiation between moderate-to-severe and mild/absent PAH by EIs, EId, and EIm resulted in AUCs of 0.738, 0.834, and 0.766, with cut-off values of 1.40, 1.34, and 1.28, respectively. A gray zone approach identified 90% sensitivity for EIs (1.12), EId (1.15), and EIm (1.23), and specificity for EIs (2.27), EId (1.32), and EIm (2.1) to rule out or diagnose moderate-to-severe PAH.ConclusionsThis study showed good inter-observer agreement of EIs, EIm, and EId measurement by ECC residents on prerecorded loops. EI allowed good identification of dogs with moderate to severe PAH by ECC residents.